Electronic structure and fermiology of LaFe2Ge2. (October 2018) - Soliman, S.
Abstract: The Density functional theory has been used to investigate the electronic structure properties of layered ternary compound LaFe2 Ge2 . The main trends in band structure, Fermi level, DOS, and charge density for the Fe2 Ge2 -layer with nonmagnetic La atom have been analyzed. The electron charge density has shown a hybridization between Fe-3d and Ge-4p causing the splitting of Fe-3d holes and electrons states which increases the Fe magnetic moment. The DOS of Fe-3d and Ge-4p orbitals has indicated that only a small set of 3d and 4p electronic states has been hybridized just under Fermi energy. Additionally, most of Fe-3d and Ge-4p states have been hybridized in the energy range from −5 eV to −2 eV. The magnetic moment of LaFe2 Ge2 is 4.96 μ B per formula unit where a localized magnetic moment of 2.54 μ B is associated with the Fe muffin-tin sphere. The Fe-4s and Ge-4s, 4p bands crossing Fermi level have formed a complicated Fermi surface for majority channel, whereas the spin down Fermi surface consists of simple narrow tubes. Highlights: DFT has been used to investigate the electronic structure of LaFe2Ge2. Fermi level, DOS and charge density have been analysed. The Fe-4s and Ge-4s, 4p bands forms the Fermi level.